Sufficient conditions for the existence of the υ -density for zeros of entire function of order zero - Zabolotskii, N. V.; Mostova, M. R. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We select the subclasses of zero-order entire functions f for which we present sufficient conditions for the existence of υ -density for zeros of f in terms of the asymptotic behavior of the logarithmic derivative F and regular growth of the Fourier coefficients of F.